A review of slicing techniques in software engineering - Shah, Asadullah; Raza, Ali; Hassan, Basri; Shah, Abdul Salam (2015)
Program slice is the part of program that may take the program off the path of the desired output at some point of its execution. Such point is known as the slicing criterion. This point is generally identified at a location in a given program coupled with the subset of variables of program. This process in which program slices are computed is called program slicing. Weiser was the person who gave the original definition of program slice in 1979. Since its first definition, many ideas related to the program slice have been formulated along with the numerous numbers of techniques to compute program slice. Meanwhile, distinction between the static slice and dynamic slice was also made. Program slicing is now among the most useful techniques that can fetch the particular elements of a program which are related to a particular computation. Quite a large numbers of variants for the program slicing have been analyzed along with the algorithms to compute the slice. Model based slicing split the large architectures of software into smaller sub models during early stages of SDLC. Software testing is regarded as an activity to evaluate the functionality and features of a system. It verifies whether the system is meeting the requirement or not. A common practice now is to extract the sub models out of the giant models based upon the slicing criteria. Process of model based slicing is utilized to extract the desired lump out of slice diagram. This specific survey focuses on slicing techniques in the fields of numerous programing paradigms like web applications, object oriented, and components based. Owing to the efforts of various researchers, this technique has been extended to numerous other platforms that include debugging of program, program integration and analysis, testing and maintenance of software, reengineering, and reverse engineering. This survey portrays on the role of model based slicing and various techniques that are being taken on to compute the slices.